Resource limitation, intra‐group aggression and brain neuropeptide expression in a social wasp. (12th August 2021) - Walton, Alexander; Toth, Amy L.
Abstract: Nourishment can have profound effects on social behaviour, including aggressive interactions between individuals. The prevailing theoretical and empirical understanding is that when nutritional resources are limited, inter‐individual competition and aggression will increase. Alternatively, studies from some group‐living species suggest limited nutrition can lead to increased cooperation, including by a reduction in inter‐individual aggression. Thus, a general model for understanding how and why nutritional resource limitation affects aggressive behaviour remains elusive. We suggest that the link between nourishment and future reproductive potential may be a key missing element of models that predict how nutritional resource availability affects inter‐individual aggression in social animals. We investigated how nourishment influenced intra‐colony aggression and its molecular correlates in colonies of the social paper wasp Polistes fuscatus, which contain workers that maintain flexible reproductive potential as adults. We subjected colonies to either a high or low feeding treatment, and examined subsequent effects on behaviour, nutritional/reproductive physiology and brain gene expression. We found that nutritional restriction reduced aggressive interactions. Thus, resource limitation was linked to reduced intra‐group conflict. Thus, individual worker paper wasps appear to have the capacity to adjust their behaviour (e.g. reduced aggression) in response to nutritional stress; this suggests they may invest nutritional resources in the colony when resources are limiting, and in the self (and possible future reproduction) when resources are abundant. Differential brain gene expression results implicate two well‐known neuropeptides associated with aggression and/or nutrient signalling across taxa, Tachykinin and Neuropeptide F, as possible mediators of nutritionally dependent intra‐colony aggression. This adds to a growing understanding that deeply conserved genes associated with core, conserved behaviours such as feeding and aggression in solitary insects can play a role in the regulation of social plasticity in more highly social species. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.